2013
DOI: 10.1007/s10067-013-2317-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interleukin-20 level in patients with systemic sclerosis: are they related with angiogenesis?

Abstract: In this study, we aimed to evaluate the relation between angiogenesis indicators and T helper 17 cytokine group in patients with systemic sclerosis (SSc) which is a disease characterized by impaired angiogenesis and autoimmune response. In our study, patients with SSc are compared with patients with primary Raynaud's phenomenon (RP) and healthy controls. Forty SSc patients, 18 primary RP cases, and 20 healthy controls were included in our study. The demographic and clinical features of patients with SSc were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Additionally, astrocytes are reported to secrete VEGF-A, and consequently modulate angiogenesis and endothelial cells barrier properties ( Krum and Rosenstein, 1998 ; Krum and Khaibullina, 2003 ; Croll et al, 2004 ; Argaw et al, 2006 , 2009 , 2012 ; Suidan et al, 2010 ; Chapouly et al, 2015 ). On the other hand, IL-20 promotes VEGF-mediated angiogenesis including other neuroinflammatory and autoimmune pathology: e.g., myasthenia gravis (MG) ( Hsieh et al, 2006 ; Hammer et al, 2009 ; Baird et al, 2011 ; Aydogdu et al, 2013 ; Alexandrakis et al, 2015 ; Han et al, 2016 ; Kako et al, 2016 ; Uzawa et al, 2016 ; Huang et al, 2018 ). Although MG is an autoimmune pathology that targets the peripheral nervous system and not the CNS, it is noteworthy that a research group reported a significant increase in IL-19 and IL-20 serum levels similar to other well characterized pro-inflammatory cytokines that impact CNS ( Uzawa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, astrocytes are reported to secrete VEGF-A, and consequently modulate angiogenesis and endothelial cells barrier properties ( Krum and Rosenstein, 1998 ; Krum and Khaibullina, 2003 ; Croll et al, 2004 ; Argaw et al, 2006 , 2009 , 2012 ; Suidan et al, 2010 ; Chapouly et al, 2015 ). On the other hand, IL-20 promotes VEGF-mediated angiogenesis including other neuroinflammatory and autoimmune pathology: e.g., myasthenia gravis (MG) ( Hsieh et al, 2006 ; Hammer et al, 2009 ; Baird et al, 2011 ; Aydogdu et al, 2013 ; Alexandrakis et al, 2015 ; Han et al, 2016 ; Kako et al, 2016 ; Uzawa et al, 2016 ; Huang et al, 2018 ). Although MG is an autoimmune pathology that targets the peripheral nervous system and not the CNS, it is noteworthy that a research group reported a significant increase in IL-19 and IL-20 serum levels similar to other well characterized pro-inflammatory cytokines that impact CNS ( Uzawa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the role of the other IL-10 family cytokines, such as IL-20 or IL-23, in the development of systemic sclerosis. Data from the literature suggests the reduced expression of IL-20 or dysregulated IL-23 signalling [ 107 , 110 ]. It remains an open question whether these findings are clinically important.…”
Section: Immunocompetent Cells In Systemic Sclerosismentioning
confidence: 99%
“…IL-20 protein levels in human biological fluids reportedly range from 60 pg/ml to 1650 ng/ml [ 10 , 14 , 15 ]. For ELISA measurements, multiple sample dilutions are required to cover this range, making reliable measurements of serum/plasma and synovial fluid (SF) IL-20 challenging.…”
Section: Introductionmentioning
confidence: 99%